A2A receptor agonists and P2Y12 receptor antagonists modulate expression of thrombospondin-1 (TSP-1) and its secretion from Human Microvascular Endothelial Cells (HMEC-1) - Gdula, Anna M.; Swiatkowska, Maria (Microvascular research, 2021)
To address the problem of resistance to standard antiplatelet therapy in some patients, our team proposed a purinoceptor-dependent dual therapy. Its efficacy is also determined by the condition of the vascular endothelium which, by secreting numerous factors, is involved in hemostasis. Among them, thrombospondin-1 is important in the context of thrombotic events. Therefore we sought to determine if the novel dual purinoceptor-dependent concept is associated with TSP-1 changes in vascular endothelial cells. TSP-1 expression in human microvascular endothelial cells was determined at transcriptional and protein level. We performed real-time PCR, the Western blot analysis and ELISA test. We found that TSP-1 mRNA and protein expression levels significantly changed in response to P1R agonists treatment. Furthermore, we have observed that co-administration of selective A2AR agonists (UK-432,097 or MRE0094) with P2Y12R antagonists altered TSP-1 expression levels, and the direction of these changes was not synergistic. MRE0094 applied with ARC69931MX or R-138727 increased mRNA expression from 39 to 56 or 57%, respectively (*P < 0.05 vs. MRE0094; ***P < 0.001 vs. control). Also, in the case of the P2Y12R antagonists used together with UK-432,097, there was an increase from 53 to 71 and 70% (*P < 0.05 vs. UK-432,097; ***P < 0.001 vs. control). The observed trends in gene expression were reflected in the protein expression and the level of its secretion from HMEC-1. The article presents evidence which proves that the purinoceptor-dependent concept is associated with TSP-1 changes in endothelial cells (EC). Moreover, Human Microvascular Endothelial Cells treatment applied together with agonists (MRE0094 or UK-432,097) and P2Y12R antagonist did not result in any synergistic effect, implicating a possible crosstalk between G proteins in GPCRs dependent signaling. Therefore, we suggest that understanding of the specific mechanism underlying TSP-1 alterations in EC in the context of the dual purinoceptor-dependent approach is essential for antiplatelet therapies and should be the subject of future research. [Display omitted] •TSP-1 mRNA and protein levels are decreased in response to the use of P1R agonists.•Simultaneous P1 agonization and P2Y12 antagonization change TSP-1 expression levels.•Antagonization of P2Y12 may alter the endothelial cell response to A2A agonists.•The dual purinoceptor-dependent approach affects the condition of endothelial cells.